2023
DOI: 10.3390/membranes13090752
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Outer Membrane Vesicles and Immune Modulation of the Host

Lily A. Charpentier,
Emily F. Dolben,
Matthew R. Hendricks
et al.

Abstract: This article reviews the role of outer membrane vesicles (OMVs) in mediating the interaction between Gram-negative bacteria and their human hosts. OMVs are produced by a diverse range of Gram-negative bacteria during infection and play a critical role in facilitating host–pathogen interactions without requiring direct cell-to-cell contact. This article describes the mechanisms by which OMVs are formed and subsequently interact with host cells, leading to the transport of microbial protein virulence factors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…CF-HBECs from three donors were exposed to either vehicle, the same number of V-OMVs, or 40% more Tobi-OMVs, to represent the increased secretion of OMVs induced by tobramycin in the in vitro experiments. The concentration of OMVs used was in the range of bacterial vesicles measured in biological fluids, including BALF, in vivo [reviewed in (28, 29)]. After a six-hour exposure, the basolateral medium was collected and cytokines were interogated by 41-plex ELISA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CF-HBECs from three donors were exposed to either vehicle, the same number of V-OMVs, or 40% more Tobi-OMVs, to represent the increased secretion of OMVs induced by tobramycin in the in vitro experiments. The concentration of OMVs used was in the range of bacterial vesicles measured in biological fluids, including BALF, in vivo [reviewed in (28, 29)]. After a six-hour exposure, the basolateral medium was collected and cytokines were interogated by 41-plex ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…OMVs were added to the apical side in a total of 500ul ALI medium. Previous studies have shown that the concentration of OMVs in biological fluids including BALF are ∼10 10 /ml (reviewed in (28, 29)). After a six-hour exposure, the basolateral media was collected for cytokine measurements.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, phage amplification in situ within bacterial biofilms, which is part of the advantages of this therapeutic alternative compared to traditional antibiotics, would probably be morphologically different, and thus, likely recognized by the respiratory epithelium using additional receptors. Phages are released from their bacterial hosts following replication along with outer membrane vesicles, which modify airway epithelial responses [ 61 , 62 ]. How mammalian cells respond to different phages following secondary rounds of replication is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These EVs contain cytoplasm, membrane molecules, and mycobacterial cell wall lipoproteins. References: Brown et al [ 28 ] (structure of bacterial membranes); Schwechheimer and Kuehn [ 29 ] and Charpentier et al [ 30 ] (vesiculation in Gram-negative bacteria); Briaud and Carrol [ 31 ] (vesiculation in Gram-positive bacteria); Gupta et al [ 32 ]; and Palacios et al [ 14 ] (vesiculation in M. tuberculosis ). Created with .…”
Section: Figurementioning
confidence: 99%